2017
DOI: 10.1002/aoc.4113
|View full text |Cite
|
Sign up to set email alerts
|

HPA decorated Halloysite Nanoclay: An efficient catalyst for the green synthesis of Spirooxindole derivatives

Abstract: A novel heterogeneous catalyst, HPA@HNTs‐IMI‐SO3H, was designed and synthesized based on functionalization of halloysite nanotubes with ionic liquid and subsequent incorporation of heteropolyacid. The structure of the catalyst was studied and confirmed by using SEM/EDX, FTIR, XRD, ICP‐AES, TGA, DTGA and BET. Moreover, the catalytic activity of HPA@HNTs‐IMI‐SO3H was investigated for promoting ultrasonic‐assisted three‐component reaction of isatines, malononitrile or cyanoacetic esters and 1,3‐dicarbonyl compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 37 publications
(45 reference statements)
0
14
0
Order By: Relevance
“…Following our attempt for disclosing efficient and eco‐friendly protocols for the synthesis of chemicals through applying novel heterogeneous catalysts, we have recently focused our attention on the functionalization of HNTs with various functionalization agents and studying the utility of functionalized HNTs as efficient support for immobilization of catalytically active species such as heteropolyacid and ionic liquids . The results of our researches as well as other research groups clearly established that the functionality on the surface of HNTs has a significant role in efficient immobilization and suppressing the leaching of the catalytic species.…”
Section: Introductionmentioning
confidence: 86%
“…Following our attempt for disclosing efficient and eco‐friendly protocols for the synthesis of chemicals through applying novel heterogeneous catalysts, we have recently focused our attention on the functionalization of HNTs with various functionalization agents and studying the utility of functionalized HNTs as efficient support for immobilization of catalytically active species such as heteropolyacid and ionic liquids . The results of our researches as well as other research groups clearly established that the functionality on the surface of HNTs has a significant role in efficient immobilization and suppressing the leaching of the catalytic species.…”
Section: Introductionmentioning
confidence: 86%
“…In the continuation of our research on disclosing the catalytic utility of Hal 23,24 , recently we have reported facile recovery and high reusability of magnetic Hal 25,26 . On the other hand, our research on the catalytic activity of IL-Hal hybrid 27,28 showed that the presence of ILs on the Hal can efficiently improve anchoring of nanoparticles and suppressing their leaching. In this work we design and synthesize a novel catalyst through multi-step procedure, Fig.…”
mentioning
confidence: 94%
“…Recently, functionalization of HNTs has been comprehensively reviewed by Riela and co‐workers . It has been shown that functionalized HNTs can be successfully used for the immobilization of various catalytically active species such as nanoparticles, heteropolyacids, ionic liquids, complexes, etc . It has been confirmed that functionalized HNTs not only can effectively suppress the leaching of supported catalytically active species but also can exert synergistic effects and improve the catalytic performance of a hybrid catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…In continuation of our studies on HNTs as catalyst supports and considering the efficiency of CDs and HNTs for immobilization of Pd, herein we report, for the first time, a novel hybrid system based on covalent conjugation of tosylated CD to thiosemicarbazide‐functionalized HNTs (HNTs‐T‐CD) for immobilization of Pd nanoparticles and the development of a novel catalyst, Pd@HNTs‐T‐CD. Considering the synthetic importance of C–C coupling reactions, we report the catalytic activity of Pd@HNTs‐T‐CD for promoting ligand‐ and copper‐free Sonogashira coupling reactions (Scheme ) and a model Mizoroki–Heck reaction (Scheme ) in a mixture of water and ethanol.…”
Section: Introductionmentioning
confidence: 99%